2018
DOI: 10.1017/jfm.2018.260
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for jet drift over topography

Abstract: The dynamics of multiple alternating oceanic jets has been studied in the presence of a simple bottom topography with constant slope in the zonal direction. A baroclinic quasi-geostrophic model forced with a horizontally uniform and vertically sheared background flow generates mesoscale eddies and jets that are tilted from the zonal direction and drift with constant speed. The governing dynamical equations are rewritten in a tilted frame of reference moving with the jets, and the cross-jet time-mean profiles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 75 publications
(114 reference statements)
7
32
0
Order By: Relevance
“…We used a two-layer QG model forced with a uniform background flow in the upper layer. In accord with previous studies (Boland et al 2012;Khatri & Berloff 2018), the jets tilt from the zonal direction and drift meridionally. Khatri & Berloff (2018) also showed that the tilted jets are coupled to the imposed background shear via the sloped topography and, in the overall balance, the jets gain energy directly from the background flow and lose energy to eddies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We used a two-layer QG model forced with a uniform background flow in the upper layer. In accord with previous studies (Boland et al 2012;Khatri & Berloff 2018), the jets tilt from the zonal direction and drift meridionally. Khatri & Berloff (2018) also showed that the tilted jets are coupled to the imposed background shear via the sloped topography and, in the overall balance, the jets gain energy directly from the background flow and lose energy to eddies.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous studies (Boland et al 2012;Khatri & Berloff 2018), the jets tilt from the zonal direction and drift meridionally because of the zonally sloped Table 1. Parameter values used in the numerical simulations.…”
Section: Model Descriptionsupporting
confidence: 92%
See 2 more Smart Citations
“…Reference [29] studied jet formation in a differentially heated rotating annulus experiment and found evidence of direct energy transfer to jets from eddies. Contrary to the upscale energy-transfer scenario, in some flow regimes jets can directly extract energy from the imposed background shear, rather than from the eddies (e.g., Reference [30]).…”
Section: Introductionmentioning
confidence: 99%